Socioeconomic status and young children's sleep/wake problems: the moderating role of maternal mindful parenting. Issue 15 (18th November 2022) - Kelly, Ryan J.; Lemberger-Truelove, Matthew E.; Martin-Cuellar, Ashley; Bagley, Erika J.; Lazzareschi, Nicholas R.; Vitanzos, Yvonnie C.; Davis, Alexandra N.
ABSTRACT: Lower socioeconomic status is related to sleep/wake problems in early childhood, however, the effects are not uniform and there is a need to understand individual differences. We examined whether maternal mindful parenting moderated this association. Participants were 172 mothers of 2- to 5-year-old children (children's M age = 3.30 years) from diverse economic and ethnic backgrounds. Socioeconomic status was indexed using income-to-needs ratio. Mothers reported on children's sleep/wake problems (insufficient sleep duration, night wakings, daytime sleepiness) and two dimensions of mindful parenting (mindful discipline, being in the moment with the child). Higher levels of maternal mindful parenting buffered the extent to which lower socioeconomic status conferred risk for children's insufficient sleep duration and night wakings. Findings build on the literature to consider sleep in the family context and illustrate that positive parenting characteristics may reduce risk for sleep/wake problems in lower socioeconomic contexts.